Innovating the practice of epilepsy care to improve patient outcomes: a model for community health worker integration - Kiriakopoulos, Elaine T.; Chu, Felicia; Jobst, Barbara C.; Kobau, Rosemarie (Frontiers in Neurology, 2025)
There is substantial evidence that community health worker (CHW) interventions can lead to improved health outcomes. However, their integration into specialty care teams—particularly within epilepsy care—is still limited. Embedding CHWs onto epilepsy center teams presents a promising opportunity to address health inequities by incorporating whole-person patient centered care and addressing social determinants of health (SDOH). The conceptual model introduced in this manuscript highlights the importance of collaboration between epilepsy centers, medical centers, health systems, community partners and nontraditional CHW professional workforce to drive systemic change. We share a process model that supports the pragmatic integration of CHWs onto epilepsy care teams and the implementation of standardized SDOH screening taking into account existing multidisciplinary professional roles and common epilepsy center frameworks for delivering care.